Genetic and management factors affecting beef quality in grazing Hereford steers - Melucci, Lilia Magdalena (2012)
Attributes contributing to differences in beef quality of 206 Hereford steers finished on pasture were assessed. Beef quality traits evaluated were: Warner–Bratzler meat tenderness and muscle and fat color at one and seven days after slaughter and trained sensory panel traits (tenderness, juiciness, flavor, and marbling) at seven days. Molecular markers were CAPN1 316 and an SNP in exon 2 on the leptin gene (E2FB). Average daily live weight gain, ultrasound monthly backfat thickness gain and rib-eye area gain were estimated. Molecular markers effects on meat quality traits were analyzed by mixed models. Association of meat quality with post weaning growth traits was analyzed by canonical correlations. Muscle color and marbling were affected by CAPN1 316 and E2FB and Warner–Bratzler meat tenderness by the former. The results confirm that marker assisted selection for tenderness is advisable only when beef aging is a common practice. The most important sources of variation in tenderness and color of meat remained unaccounted for.